EXCESSIVE LIFESTYLE ACCORDING TO AL MUNIR TAFSIR BY WAHBAH AZ ZUHAILI - Dodi Robiansyah; Burhan Lukman Syah; Alip Eko Pasetyo; Aqila Najiha Mohd Afandi (Universitas Muhammadiyah Surakarta, 2023)
Lifestyle is a person's way of socializing to meet their needs with others, a person's behavior will be formed related to the image of a person to show his social status. There are many verses of the Qur'an that describe excessive style. The author takes the verse of QS. Al-A'raf: 31, Q.S Al-Isra':26-27, QS. Al-An'am: 141, along with the development of science, many people have researched excessive lifestyles from various perspectives, but to be more convincing, the author takes the perspective of Wahbah Az- Zuhaili's Tafsir Al-Munir. The purpose of this study is to find out how the interpretation of Wahbah Az-Zuhaili in Tafsir Al-Munir on the Excessive Lifestyle of Norman Fairclough's discourse analysis perspective. This research uses descriptive qualitative with the type of literature research, the source of data used is Tafsir Al-Munir by Wahbah Az zuhaili, books, journals and literature related to excessive lifestyle. Data collection techniques use documentation techniques, and data analysis techniques researchers perform a mufassir analysis of excessive lifestyle verses. Based on the results of this study, the validity of an excessive lifestyle is an act that is not liked by God because it is a wasteful act and can be punished as haram.